Кумулятивные особенности полиоксипропиленполиолов = Cumulative features of polyoxypropylenepolyols. - Babienko, V. V.; Anischenko, L. V.; Mykhaylenko, V. L. (Journal of Education, Health and Sport, 2016)
Babienko V. V., Anischenko L. V., Mykhaylenko V. L. Кумулятивные особенности полиоксипропиленполиолов = Cumulative features of polyoxypropylenepolyols. Journal of Education, Health and Sport. 2016;6(9):867-872. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.161687 http://ojs.ukw.edu.pl/index.php/johs/article/view/3941 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.09.2016. Revised 24.09.2016. Accepted: 30.09.2016. КУМУЛЯТИВНЫЕ ОСОБЕННОСТИ ПОЛИОКСИПРОПИЛЕНПОЛИОЛОВ В. В. Бабиенко, Л. В. Анищенко, В. Л. Михайленко Одесский национальниый медицинский университет Одесса, Украина CUMULATIVE FEATURES OF POLYOXYPROPYLENEPOLYOLS V. V. Babienko, L. V. Anischenko, V. L. Mykhaylenko Odessa National Medical University, Ukraine Cumulative features of polyoxypropylenpolyols on experiment animals were investigated in the article. As a result was established that polyols in the case of a single dose ingestion on warm-blooded animals can disturb hemodynamics mainly in the brain, liver, kidney, spleen, heart and cause of parenchymal organs dystrophy. Key words: polyoxypropylenpolyols, cumulative features, warm-blooded animals.